Sustainable Energy as a Sine Qua Non Condition for the Achievement of Sustainable Development - Pawłowski, Artur (Problemy Ekorozwoju, 2009)
any attempt to make the principle of inter-generational justice a reality will be utterly dependent on the appropriate management and utilization of energy carriers. In other words, the principles of sustainable development will not be put into effect unless sustainable energy use is introduced, and that will require wide application of renewable sources, notably the wind, sun, geothermal resources, biowastes, biomass and biogas. The greatest progress in this area noted to date has been that of the EU Member States, whose joint achievement in the period 1990-2003 inclusive was to quintuple the amount of energy generated from renewable sources, most especially biomass and the wind.